Effect of the Indonesian scientific exercise guidelines for adults with spinal cord injury on quality of life in patients with chronic spinal cord injury - Ega Rahman Evsya; Lydia Arfianti; Nurul Kusuma Wardani; Dewi Poerwandari; Inggar Narasinta (Universitas Udayana dan Diaspora Taipei Medical University, 2026)
Background: Spinal cord injury (SCI) impairs motor and autonomic function and is often associated with reduced quality of life (QOL). Although the Scientific Exercise Guidelines for Adults with Spinal Cord Injury (SEG-SCI) have been shown to improve fitness and QOL, their effectiveness has not been evaluated in Indonesia. This study examined the effect of implementing the Indonesian adaptation of SEG-SCI on QOL in individuals with chronic SCI. Methods: A randomized controlled trial with a pre–post design was conducted in seventeen individuals with chronic SCI. Participants were randomly allocated to the control group (n= 9) and intervention group (n= 8). The intervention group completed a 12-week exercise program based on the Indonesian version of SEG-SCI in addition to usual care, and control group underwent observation at the start and at the end of the study. QOL was assessed using the SF-36 before and after the intervention. Results: Five people (45%) in the control group and six people (55%) in the intervention group said they did moderate amounts of physical activity every day, according to activity diary records. Participants in the intervention group showed a significant improvement in QOL, with a mean increase of 13.12 ± 6.7 points on the SF-36 (p = 0.001, d = 1.19), whereas the control group showed negative change of -7.5 ± 4.71 after a 12-week intervention period (p = 0.001, d = 0.44). Conclusion: A 12-week exercise program based on the Indonesian adaptation of SEG-SCI safely improves quality of life in individuals with chronic SCI. Participants who followed the guideline-based program showed clinically relevant improvements, whereas those in the control group, who did not receive structured exercise, experienced a decline in quality of life over the same period.